2020
DOI: 10.1111/ejn.14906
|View full text |Cite
|
Sign up to set email alerts
|

Temporal associations between sleep slow oscillations, spindles and ripples

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 70 publications
8
39
0
Order By: Relevance
“…Similar to previous observations in dHPC (Maingret et al, 2016; Molle et al, 2006; Oyanedel et al, 2020; Peyrache et al, 2011; Peyrache et al, 2009; Sirota et al, 2003), vHPC SWR occurrences were moderately increased around UP–DOWN transitions (reached maxima 105 ± 88 ms prior to delta peaks in post-cond. NREM, n= 14 rats; Figure 4I).…”
Section: Resultssupporting
confidence: 89%
“…Similar to previous observations in dHPC (Maingret et al, 2016; Molle et al, 2006; Oyanedel et al, 2020; Peyrache et al, 2011; Peyrache et al, 2009; Sirota et al, 2003), vHPC SWR occurrences were moderately increased around UP–DOWN transitions (reached maxima 105 ± 88 ms prior to delta peaks in post-cond. NREM, n= 14 rats; Figure 4I).…”
Section: Resultssupporting
confidence: 89%
“…Thus, the positive and subsequent negative threshold crossing represented the onset and end of a spindle event, respectively. Previous studies showed that with this criteria larger spindle events are identified that typically occur in parallel in both hemispheres (e.g., Oyanedel et al, 2020).…”
Section: Detection Of Sleep Slow Oscillations and Spindlesmentioning
confidence: 99%
“…Slow waves (SWs) are the predominant cortical rhythm during nonrapid eye movement sleep and anesthesia ( 1 , 2 ). Since they were first characterized three decades ago, SWs have been linked to a variety of brain functions, including memory consolidation ( 3 6 ), homeostatic synaptic plasticity ( 7 ), and grouping of other oscillatory events ( 8 10 ). Macroscopic recordings (scalp electroencephalogram [EEG]) have revealed that spontaneous global SWs occur approximately once per second (∼1 Hz) and propagate in a stereotypical front-to-back topography through the entire cortex ( 11 ).…”
mentioning
confidence: 99%